All Creatures : Naturalists, Collectors, and Biodiversity, 1850-1950 - Kohler, Robert E. (Book collections on Project MUSE., 2006)
"Here a historian of science tells the story of the modern discovery of biodiversity. Robert Kohler argues that the work begun by Linnaeus culminated around 1900, when collecting and inventory were organized on a grand scale in natural history surveys. Supported by governments, museums, and universities, biologists launched hundreds of collecting expeditions to every corner of the world. Kohler conveys to readers the experience and feel of expeditionary travel: the customs and rhythms of collectors' daily work, and its special pleasures and pains."--Jacket.